AGRARIAN CONFLICT OVER LAND OF PT. INDONESIAN RAILWAYS IN LANGKAT: AN ANALYSIS OF POSITIVE LAW AND ISLAMIC LAW - Ahmad Faruqi; Dhiauddin Tanjung; Hasan Matsum (SOSIOEDUKASI, 2025)
The issue of land use by PT. Kereta Api Indonesia (Persero) in Langkat Regency from the perspective of positive law and Islamic law. The main problem lies in the widespread use of land owned by PT. KAI by the community without legal permission, which has led to conflicts over land ownership and control. From the perspective of positive law, this study examines the legal basis for PT. KAI's ownership of the land under Law No. 5 of 1960 on the Basic Principles of Agrarian Law (UUPA), Law No. 23 of 2007 on Railways, and Ministry of State-Owned Enterprises Regulation No.PER-13/MBU/09/2014 on Guidelines for the Management of State-Owned Enterprises' Fixed Assets. These provisions affirm that land assets owned by PT. KAI are part of the state's wealth, managed professionally, and protected by law. This study employs a normative and empirical approach. The normative approach is used to analyze the legal provisions governing the status and management of land, while the empirical approach is conducted through field studies and interviews to uncover the social dynamics and actual practices of land utilization. The normative approach is used to examine the legal provisions governing the status and management of land, while the empirical approach is conducted through field studies and interviews to uncover the social dynamics and actual practices of land utilization. The analysis revealed that weak supervision and the absence of an effective social approach have led to many residents unlawfully occupying or utilizing land. From an Islamic legal perspective, such actions From an Islamic legal perspective, such actions contradict the principles of al-amanah (trust), al-milkiyyah (property rights), and ‘adalah (justice), and are inconsistent with the concept of tasarruf which requires that the right to utilize land be exercised lawfully and without harming others. This study recommends the enforcement of strict yet humane laws by PT. KAI, accompanied by mediation and consultation with the community. Harmonization between positive law and Islamic legal values Harmonization between legal and Islamic legal values needs to be strengthened to create fair, sustainable, and humanitarian resolutions to agrarian conflicts.